Cruciferous Vegetables and Risk of Cancers of the Gastrointestinal Tract. Issue 18 (30th April 2018) - Johnson, Ian T.
Abstract: Cancers of the oropharyngeal tissues, oesophagus, stomach, and colorectum are amongst the most common causes of death from cancer throughout the world. Higher consumption of fruits and vegetables is thought to be protective, and cruciferous vegetables are of particular interest because of their unique role as a source of biologically active glucosinolate breakdown products. A literature review of primary studies and meta‐analyses indicates that higher consumption of cruciferous vegetables probably reduces the risk of colorectal and gastric cancers by approximately 8% and 19%, respectively. Some studies support the hypothesis that the protective effect against colorectal cancer is modified by genetic polymorphisms of genes regulating the expression of enzymes of the glutathione S ‐transferase family, but due to contradictory findings the evidence is currently inconclusive. Despite these promising findings, future epidemiological research on the protective effects of cruciferous plants will depend critically upon accurate measurement of dietary exposure, both to the vegetables themselves, and to their active constituents. The development of sensitive chemical assays has facilitated the measurement of urinary excretion of isothiocyanate metabolites as an objective biomarker of intake, but sampling strategies need to be optimized in order to assess long‐term exposures at the population level. Abstract : Higher consumption of cruciferous vegetables may protect against cancers of the gastrointestinal tract. A literature review of primary studies and meta‐analyses indicates protective effects of 8% and 19% for colorectal and gastric cancers, respectively. Some studies suggest that these protective effects are modified by common genetic polymorphisms of genes for the glutathione S ‐transferase enzyme family but the evidence remains inconclusive.